RESEARCH ANALYSIS OF SMALL BUSINESS AND ITS SUSTAINABLE DEVELOPMENT (British Journal of Global Ecology and Sustainable Development, 2023)
The article presents the concept of small business, its specific aspects. At the same time, scientific studies of foreign and domestic scientists related to the concept of sustainable development, as well as the sustainable development of small businesses, were studied and analyzed. On the basis of the analysis carried out, the author's definitions of these concepts are given.